The role of chronic endometritis in the aspect of habitual miscarriage in patients with adenomyosis - E. I. Kravtsova; I. N. Lukoshkina; L. B. Miroshnichenko; Y. V. Nicogda; I. I. Kravtsov (Медицинский вестник Юга России, 2023)
Objective: to identify the presence of chronic endometritis in patients with adenomyosis and its cumulative role in the formation of reproductive losses.   Materials and methods: 101 women of reproductive age with grade II adenomyosis and habitual miscarriage were examined. The comparison group (group 2) consisted of 49 patients with grade II adenomyosis without a history of early reproductive losses. The control group (group 3) consisted of 50 healthy patients. In order to diagnose chronic endometritis, a comprehensive immunohistochemical study of the expression of specific immunological markers of chronic endometritis (natural killer CD56, B cells (CD20), plasma cells (CD138) and activated lymphocytes (HLA-DR) with antibodies and the determination of CD68 macrophages was carried out. Polymerase chain reaction in the “real-time” mode (PCR) was used to determine the types and amount of endometrial microbiota. Statistical data processing was carried out in the environment of the STATISTICA package.   Results: despite the absence of pathogenic and conditionally pathogenic microflora, according to the results of microbiological examination from the vagina and cervical canal of all examined patients, statistically significant differences in the detection frequencies of various microbiota taxa of crops from the uterine cavity were obtained. Patients with reproductive losses on the background of adenomyosis had microbiological and immunohistochemical signs of chronic endometritis of moderate and mild severity. The presence of chronic endometritis combined with adenomyosis contributes to the occurrence of pronounced endothelial dysfunctions, eventually leading to a violation of reproductive function in patients with a combination of HE and adenomyosis.   Conclusion: The similar symptoms of adenomyosis and CE, a reliable association of adenomyosis with CE in patients with habitual miscarriage requires the inclusion of immunohistochemical and microbiological examination of the endometrium in the volume of pre-gravidar examination, even if there are negative results of microbiological examination of the environment of the cervical canal.